Front-End Module of 18–40 GHz Ultra-Wideband Receiver for Electronic Warfare System - Yuseok Jeon; Sungil Bang (Journal of the Korean Institute of Electromagnetic Engineering and Science, 2018)
In this study, we propose an approach for the design and satisfy the requirements of the fabrication of a small, lightweight, reliable, and stable ultra-wideband receiver for millimeter-wave bands and the contents of the approach. In this paper, we designed and fabricated a stable receiver with having low noise figure, flat gain characteristics, and low noise characteristics, suitable for millimeter-wave bands. The method uses the chip-and-wire process for the assembly and operation of a bare MMIC device. In order to compensate for the mismatch between the components used in the receiver, an amplifier, mixer, multiplier, and filter suitable for wideband frequency characteristics were designed and applied to the receiver. To improve the low frequency and narrow bandwidth of existing products, mathematical modeling of the wideband receiver was performed and based on this spurious signals generated from complex local oscillation signals were designed so as not to affect the RF path. In the ultra-wideband receiver, the gain was between 22.2 dB and 28.5 dB at Band A (input frequency, 18–26 GHz) with a flatness of approximately 6.3 dB, while the gain was between 21.9 dB and 26.0 dB at Band B (input frequency, 26–40 GHz) with a flatness of approximately 4.1 dB. The measured value of the noise figure at Band A was 7.92 dB and the maximum value of noise figure, measured at Band B was 8.58 dB. The leakage signal of the local oscillator (LO) was −97.3 dBm and −90 dBm at the 33 GHz and 44 GHz path, respectively. Measurement was made at the 15 GHz IF output of band A (LO, 33 GHz) and the suppression characteristic obtained through the measurement was approximately 30 dBc.